WAYS OF INCREASING THE EFFICIENCY OF INDUSTRIAL ENTERPRISES IN THE INNOVATIVE DEVELOPMENT OF THE SERVICE FIELD IN THE DIGITAL ECONOMY - Oltaev Sh.S, (TADQIQOTLAR, 2026)
Abstract: This article examines ways to improve the efficiency of industrial enterprises in the innovative development of the service sector in the digital economy. The  article  also  discusses  the  importance  of  constantly  monitoring  changes  and adapting  the  strategy  to  new  challenges  and  opportunities.  The  main  factors  that emphasize  the  need  for  this  approach  are  discussed,  such  as  a  dynamic  market, customer needs, the competitive environment, and technological advances. The authors emphasize that constant monitoring and adaptation of the strategy allows companies to be agile, innovative, and competitive, ensuring successful development in the long term.